Impaired Liver Regenerative Response Following Administration Of Anti-TLR4 Antibody In Mice - Marlini Muhamad; A. Mabuchi; B. Mallard; N. Hairulhisyam; S. Akashi-Takamura; H. Miyata; J. Harper; A. Wheatley (Elsevier, 2024)
VOLUME 64, ISSUE 2